THE SCHOOL'S EFFORTS IN BECOMING AN INVOLVED PARTY IN THE SOCIALIZATION OF STUDENT CHARACTER FORMATION - Dina Destari (Indonesian Journal of Education (INJOE), 2023)
This literature review aims to look at the school's efforts to become a party involved in the socialization of student character formation. Schools are formal educational institutions where learning and teaching activities take place where children of the same age will interact and socialize with each other so that schools also act as agents of socialization. School is a socialization agent that enables an individual to be able to socialize in a wider environment, namely in the community. The efforts made by the school as a party involved in socialization in forming students' character include instilling a disciplined attitude, forming attachments to social groups, and fostering autonomy. Moral discipline really determines the character and personality of students in general. In fostering a disciplined attitude, schools implement rules and regulations with the aim of making students more disciplined, orderly, ethical, and forming student character. Meanwhile, the obstacles faced by schools in forming student character are obstacles that originate from within the student, obstacles that originate from the family environment, and obstacles that originate from peers.